Unaccustomed as I am to public speaking - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
series of training seminars organised by CTA in Cape Verde in September, and in Mali, Namibia and Uganda in November 2000